RESPON PASAR TERHADAP SURPRISE PROFITTABILITAS: ANALISIS PADA LAPORAN KEUANGAN TRIWULAN DAN TAHUNAN - , Ismayantika Dyah Puspasari ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Every company has a purpose in carrying out its operations both in providing services for the production of goods and services. Basically the main aim of the company is to maximize shareholder wealth. Earnings announcement is timely and relevant to the individual that is in the stock market where the market reacts to earnings because earnings have information content. The information in each financial period will be different and would be respond by the market differently. Sampling technique in this study was purposive sampling to study the subject at LQ 45 companies listed in Indonesia Stock Exchange. This study describes the causality correlation classified causal link, between the earnings surprise variable to abnormal stock returns with dummy regression analysis method. Sources of data is used in this study are secondary data obtained from the Stock Exchange, the World Investment and Financial Statements LQ 45 firms in 2010-2012. The results showed (1) operating earnings surprises significant positive effect on abnormal stock returns, (2) net earnings surprise without extraordinary income significantly negative effect on abnormal stock returns, (3) net earnings surprise significantly negative effect on abnormal stock returns, (4) the market response to the annual financial statements are weaker than the quarterly financial statements. This study provides a view that operating earnings surprise able to properly describing its relationship to abnormal stock returns that responded significantly by market. In addition, this study provides new results that quarterly financial statements responded more strongly by the market. Because earnings in 2010 can not be compared with 2011 earnings will be better if the variable net profit without extraordinary income shock is replaced by free variables comprehensive income using data earnings surprise in early 2011 as a replacement in 2010.